KARAKTERISTIK MASYARAKAT MUSLIM DALAM PROGRAM MUSLIM TRAVELERS DI NET TV EPISODE “SENANDUNG ISLAM DI GLASGOW, SKOTLANDIA - Nanda Mustika Furstin; Ahmad Subakir; Ropingi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
Framing is described as an analysis to find out how reality (events, actors, groups, or whatever) is framed and presented by the media. The presentation emphasizes two things, namely the selection of issues and the prominence of certain aspects of reality / issues. By making information clearer, more meaningful, and more meaningful, the highlighted reality has a great possibility to be more noticed and remembered, so that it can influence the audience in understanding a reality. Muslim Travelers is a documentary format program that elevates the lives of Muslims in a country where the majority of people are non-Muslim. The depiction of Muslims in a non-Muslim majority country depends on how the media presents the information. How broad the media describes the reality of Muslim minority life framed and broadcast on television, and how we see and understand the reality shown is strongly influenced by the media.This study aims to find out how the characteristics described in the Muslim Travelers program on NET. Tv episode of Senandung Islam di Glasgow, Skotlandia. Researchers used a descriptive qualitative approach with data analysis method by Robert M. Entman Framing Analysis. With observation, documentation and data collection methods for Muslim program NET program producers. Tv. As a result of this study, researchers found that the characteristics of the Muslim community in the Muslim Travelers program on NET Tv episodes of the Senandung Islam di Glasgow, Skotlandia are the character of Muslim communities whose members are fully based on a strong faith. Faith is the foundation of all the activities and behaviors that the Muslim community in Glasgow shows. The character of the Muslim community in Glasgow shows each of its members working together and commanding each other to those who are ma’ruf or all forms of kindness and stay away from kemunkaran or contrary to religious values. The character of the Muslim community in Glasgow also manifested in their activities and activities namely deliberation. Upholding the values of justice and maintaining and establishing brotherhood, the brotherhood meant is not only limited to fellow Muslims but with non-Muslim communities. As well as the magnitude of the tolerance attitude they showed in various ways. Tolerance is an important part in maintaining good relations with fellow communities in Glasgow.